2007
DOI: 10.1152/ajprenal.00185.2007
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of TRPC6 protein expression by high glucose, a possible mechanism for the impaired Ca2+signaling in glomerular mesangial cells in diabetes

Abstract: The present study was performed to investigate whether transient receptor potential (TRPC)6 participated in Ca 2ϩ signaling of glomerular mesangial cells (MCs) and expression of this protein was altered in diabetes. Western blots and real-time PCR were used to evaluate the expression level of TRPC6 protein and mRNA, respectively. Cell-attached patch-clamp and fura-2 fluorescence measurements were utilized to assess angiotensin II (ANG II)-stimulated membrane currents and Ca 2ϩ responses in MCs. In cultured hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 44 publications
5
77
0
Order By: Relevance
“…Kidneys and liver were removed after rats were anesthetized. Glomeruli were isolated as described in our previous publication (17). The isolated glomeruli and a piece of homogenized liver tissue (ϳ100 mg) were solubilized in lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Kidneys and liver were removed after rats were anesthetized. Glomeruli were isolated as described in our previous publication (17). The isolated glomeruli and a piece of homogenized liver tissue (ϳ100 mg) were solubilized in lysis buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Trpc6 KO mice showed an elevated blood pressure and increased vascular smooth muscle contractility that was only partly recovered by the constitutively-active TRPC3-type channels, which are up-regulated in the smooth muscle cells of Trpc6 KO mice (Dietrich et al 2005). Lastly, TRPC6 channel activity at the slit diaphragm is shown to be essential for proper regulation of podocyte structure and function (Reiser et al 2005;Graham et al 2007). The functional role of TRPC7 is still unclear, but it is suggested that TRPC7 conducts Ca 2þ in AT1-induced myocardial apoptosis via a calcineurin-dependent pathway and can thereby contribute to the process of heart failure (Satoh et al 2007).…”
Section: Trpcsmentioning
confidence: 99%
“…22 In addition, TRPC6 expression is downregulated by high glucose; thus, modulation of TRPC6 may play a role in the cardiovascular complications of diabetes. 23 The present study expands our understanding of the roles of TRPC6 in endothelial biology to include a role as an EET effector, and suggests that a loss of EET signaling may partially explain the detrimental effects of TRPC6 dysregulation. Furthermore, this study suggests that targeted pharmacological intervention to enhance TRPC6 or EET function may be useful for improving endothelial function.…”
Section: Larsen Et Almentioning
confidence: 55%